Reversed-phase chromatography as an effective tool for the chiral separation of anionic and zwitterionic carboranes using polysaccharide-based chiral selectors - Horáček, Ondřej; Marvalová, Jana; Štilcová, Kristýna; Holub, Josef; Grüner, Bohumír; Kučera, Radim (Journal of chromatography. A, 2022)
The aspect of the different spatial arrangement of anionic cobalt bis(dicarbollides) and dicarba-nido-undecaboranes remains grossly overlooked despite increased scientific interest. Regarding their growing potential, which does not limit only to medicinal chemistry, suitable enantioseparation methods are needed. The presented paper explores the possibilities of chiral separations of anionic cobalt bis(dicarbollide) and dicarba-7,8-nido-undecaborane derivatives on four polysaccharide-based columns under reversed-phase conditions. The chromatographic behavior of anionic derivatives was evaluated and compared with that of zwitterionic clusters. The isocratic procedure for HPLC method development was suggested. The main parameters for the optimization of separations were described. Successful chiral separations were critically compared to previously reported results in normal phase and polar-organic mode. Reversed-phase separations are superior in resolution, lower consumption of organic solvents, and flexibility during the method development. Moreover, the first chiral discrimination of some hydroxyalkyl derivatives of anionic cobalt bis(dicarbollides) is reported. The outcomes of this work may be used for method development in any area, where the chirality of these interesting molecules is of concern.
Keywords: vysokoúčinná kapalinová chromatografie; polysacharidy; Reversed-phase; Chiral separation; anionty; Chromatography, High Pressure Liquid; Anions; Boron clusters; Carboranes; HPLC; kobalt; Cobalt; chromatografie s reverzní fází; Chromatography, Reverse-Phase; Stereoisomerism; stereoizomerie; Polysaccharides